Pembinaan Bahasa Indonesia melalui Analisis Salah Kaprah pada Website 20detik dan Koran Harian Mistar: Kajian Morfofonemik - Evin Rohmahaldo Purba; Diana Wati Sinaga; Elli Novita Hutasoit (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to identify and analyze the use of malapropistic words on the 20Detik Website and Harian Mistar Newspaper based on a morphophonemic study. This research employed a qualitative descriptive method with data collection techniques in the form of documentation studies through screenshots of news articles from the 20Detik Website and Harian Mistar Newspaper. The data were analyzed based on Indonesian morphophonemic rules, particularly the processes of phoneme changes, additions, and deletions in word formation. The results showed that eleven forms of malapropistic words were found on the 20Detik Website, namely mempesona, merubah, mengkonsumsi, mengkonfirmasi, mengkoreksi, mengkoordinasikan, mempraktekkan, pengrajin, mengkoleksi, mentasbihkan, and menterjemahkan. Meanwhile, one form of malapropistic word was found in the Harian Mistar Newspaper, namely menghimbau. These errors were generally caused by inconsistencies in applying morphophonemic rules, especially in the phoneme deletion process involving the meN- and peN- prefixes. The findings indicate that mass media have not fully implemented standard Indonesian language rules consistently. Therefore, continuous language development is needed through increased accuracy among writers and editors, the use of the KBBI as the primary reference, and strengthening language awareness so that mass media can serve as a model for proper and correct Indonesian usage in society.